Jaarlijkse vrouwendag in Gebouw voor Kunsten en Wetenschappen. V.l.n.r.: Ploeg, Martha Kethly, Anna Kethly en Vermeer
Jaarlijkse vrouwendag in Gebouw voor Kunsten en Wetenschappen. V.l.n.r.: Ploeg, Martha Kethly, Anna Kethly en Vermeer.